Physics - Booth, Graham, 1950- (London : Letts Educational, 2004)
The 'Revise A2' study guides are written by examiners and contain in-depth course coverage of the key information plus hints, tips and guidance. End of unit sample questions and model answers provide essential practice to improve students exam technique.
Previous ed.: 2001.
Includes index.
Keywords: Physics; Physics -- Examinations -- Study guides; Popular Science and Mathematics